A Facile Approach to Fabricating Antibacterial Textile with High Efficiency and Compact Process. Issue 21 (10th October 2021) - Li, Linfeng; Yu, Pengju; Li, Yuanyuan; Wu, Xi; Li, Wenbin; Cheng, Xiaomin
Abstract: The urgent need of healthcare promotes the research and development of antibacterial textiles. However, conventional antibacterial textile is based on the solution method to form bacteriostatic granules on the textile matrix, and this form of textile has lurking perils to environment and low durability. Herein, a distinctive self‐limiting surface chemical reaction, atomic layer deposition (ALD), is proposed that deposit zinc oxide (ZnO) on cotton fabrics pretreated with polydopamine (PDA) to prepare nanocomposite textiles in an exceedingly short time by meticulously regulating the parameters. The results show that the cotton @ PDA treated for only 10 min has more than 95% antibacterial rate against both S. aureus and E. coli, which is better than that treated by ALD or PDA alone. Besides, the significance of reactive oxygen species in the antibacterial activity of PDA and ZnO composite coating is confirmed by introducing vitamin E for the first time. Thanks to PDA pre coating and the unique interface combination mode of ALD, the antibacterial textiles introduced in this study have excellent durability. The strategy proposed in this paper can provide a theoretical basis for the antibacterial modification of medical devices. Abstract : An antibacterial fabric is obtained by polydopamine (PDA) and atomic layer deposition (ALD) treatment. The cotton fabric @ PDA treated with only 10 ALD cycles has excellent antibacterial activities and durability. The addition of vitamin E confirms the importance of reactive oxygen species in antibacterial activity.